Impact of Hyperferritinemia on Immune Modulation in Septic Diabetic Patients - Min-Ji Kim; Eun-Jung Choi; In-Kyu Lee (Diabetology, 2024)
Diabetes significantly impacts the immune system; however, its role in worsening sepsis prognosis remains poorly understood. This study investigated the effect of hyperferritinemia on immune modulation in septic diabetic patients. A cohort study at Kyungpook National University Hospital stratified sepsis patients by diabetes status and followed them for 28 days. Additionally, CD4+ T cells from mice were analyzed for proliferation, apoptosis, and metabolic changes under ferritin treatment. Results from the clinical study showed higher ferritin levels in diabetic patients, and those with lower lymphocyte counts had increased mortality. In the mice study, ferritin inhibited T cell activation and proliferation by shifting metabolism from glycolysis to oxidative phosphorylation without increasing cell death. These findings suggest that the suppression of T cell proliferation due to elevated ferritin levels contributes to an immunosuppressive environment, leading to worse outcomes. In conclusion, hyperferritinemia is a biomarker for sepsis severity, particularly in diabetic patients, highlighting potential therapeutic strategies targeting ferritin levels or glycolytic pathways.